International monetary and financial relations: structure of a distance course for bachelors - Totska, Olesia Leontiivna (Харківський національний університет імені В. Н. Каразіна, 2025)
The structure of the distance learning course "International Monetary and Financial Relations" is described. Описано структуру дистанційного курсу «Міжнародні валютно-фінансові відносини».
Keywords: international monetary and financial relations; міжнародні валютно-фінансові відносини; 339:004.9